2014
DOI: 10.1002/jbmr.2248
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Obstructive Pulmonary Disease and Smoking Status With Bone Density and Vertebral Fractures in Male Lung Cancer Screening Participants

Abstract: We studied the vertebral fracture prevalence on low-dose chest computed tomography (CT) in male lung cancer screening participants and the association of fractures and bone density with chronic obstructive pulmonary disease (COPD) and smoking. 1140 male current and former smokers with !16.5 packyears from the NELSON lung cancer screening trial were included. Age, body mass index, and smoking status were registered. CT scans and pulmonary function tests were obtained on the same day. On CT, vertebral fractures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
4
31
2
Order By: Relevance
“…In a large study, the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE), researchers failed to demonstrate an association of reduced bone attenuation values with COPD after adjusting for smoking history and demographics. More recently, however, a subset of men from the Dutch-Belgian Randomized Lung Cancer Screening Trial (i.e., the NELSON study) was noted to have an association of bone attenuation values obtained by computed tomography (CT) as a surrogate for bone mineral density (BMD) with COPD status after adjusting for age and smoking (7). The explanations for an association of osteoporosis and COPD are not well defined, but they potentially include smoking effects on bone (5,8), inactivity (1), nutritional deficits, glucocorticoid use (9), and chronic inflammation (10,11).…”
mentioning
confidence: 98%
“…In a large study, the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE), researchers failed to demonstrate an association of reduced bone attenuation values with COPD after adjusting for smoking history and demographics. More recently, however, a subset of men from the Dutch-Belgian Randomized Lung Cancer Screening Trial (i.e., the NELSON study) was noted to have an association of bone attenuation values obtained by computed tomography (CT) as a surrogate for bone mineral density (BMD) with COPD status after adjusting for age and smoking (7). The explanations for an association of osteoporosis and COPD are not well defined, but they potentially include smoking effects on bone (5,8), inactivity (1), nutritional deficits, glucocorticoid use (9), and chronic inflammation (10,11).…”
mentioning
confidence: 98%
“…This would allow for identification of patients at risk for future fractures on CT examinations that are performed for other indications [6,7] as bone density measured on CT is correlated with DXA measurements [8][9][10]. In addition, other studies showed that bone density measured on CT was lower in participants when a vertebral fracture is present, suggesting bone density could predict fracture risk [11][12][13]. As osteoporosis can be treated at an early stage, theoretically fractures could be avoided through opportunistic screening and treatment, yet a formal outcome study is required to prove it in this setting [1,14].…”
Section: Introductionmentioning
confidence: 95%
“…(12,18,22) The prevalence of radiographic VFs in subjects with COPD as reported in the literature is varying between 9.0% and 79%, (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) with the prevalence of radiographic VFs in subjects with COPD increasing from 32% to 52% in a 3-year time period. (32) However, the incidence of clinical VFs in subjects with COPD was as low as 1.3/1000 person-years (35) to 6% over 2.6 years (36) and 0.5% to 1.0% within 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…(32) However, the incidence of clinical VFs in subjects with COPD was as low as 1.3/1000 person-years (35) to 6% over 2.6 years (36) and 0.5% to 1.0% within 3 years. (37) Smokers without COPD have lower BMD, (38) an increased risk of VFs, (11,24,34,38,39) and an increased risk of any osteoporotic fracture. (10,39) The prevalence of radiographic VFs in smokers as reported in the literature varied between 11% and 24%, (34,38) whereas incidence of clinical VFs varied from 3% (40) (30-year follow-up) to 26% (39) (10-year follow-up).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation